1998
DOI: 10.1507/endocrj.45.285
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-Up of a 46,XY Phenotypic Girl with 17.ALPHA.-Hydroxylase Deficiency Treated with Alternate-Day Dexamethasone.

Abstract: Abstract.We report an 18-year-old 46,XY phenotypic girl who has been on alternate-day dexamethasone therapy for 10 years. The patient was seen at our hospital for right-sided inguinal hernia at the age of 4 years. Biopsy of the herniated gonad showed testicular tissue, and the karyotype of the peripheral lymphocytes was 46,XY. The diagnosis of 17a-hydroxylase deficiency was established by the evaluation of adrenal steroidogenesis at the age of 6.1 years when hypertension was clearly recognized, and was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Satoh et al. reported a 46,XY phenotypic girl who was diagnosed with17-OHD at the age of 6 years because of hypertension, whereas medical history showed that she had right-sided inguinal hernia at the age of 4 years ( 15 ). Likewise, Camtosun et al.…”
Section: Discussionmentioning
confidence: 99%
“…Satoh et al. reported a 46,XY phenotypic girl who was diagnosed with17-OHD at the age of 6 years because of hypertension, whereas medical history showed that she had right-sided inguinal hernia at the age of 4 years ( 15 ). Likewise, Camtosun et al.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is a Japanese phenotypic female, whose clinical course had been reported in detail previously [24]. The patient was noticed to have high blood pressure and low serum potassium levels when she developed Kawasaki disease at the age of 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…Several pieces of circumstantial evidence argue for the effects of adrenal androgens on BA. First, delayed BA before pubertal onset in a case of complete adrenal androgen deficiency suggests that adrenal androgens are involved in prepubertal bone maturation, as was apparently the case in a Japanese female patient with the 46,XY karyotype with 17a-hydroxylase deficiency, whose BA at the chronological age (CA) of 10 years was 6 years for a female, and 7 years for a male, child (22).…”
Section: Adrenarche and The Bone Maturationmentioning
confidence: 99%